Dysembryoplastic Neuroepithelial Tumors Share with Pleomorphic Xanthoastrocytomas and Gangliogliomas BRAFV600E Mutation and Expression. (20th March 2013) - Chappé, Céline; Padovani, Laetitia; Scavarda, Didier; Forest, Fabien; Nanni‐Metellus, Isabelle; Loundou, Anderson; Mercurio, Sandy; Fina, Frédéric; Lena, Gabriel; Colin, Carole; Figarella‐Branger, Dominique
Abstract Pediatric cortical glioneuronal benign tumors mainly include gangliogliomas (GG) [differential diagnoses pilocytic astrocytomas (PA) and pleomorphic xanthoastrocytomas (PXA)] and dysembryoplastic neuroepithelial tumor (DNT). DNT include the specific form and the controversial non‐specific form that lack the specific glioneuronal element. Our aims were to search for BRAFV600E mutation and CD34 expression in DNT, PXA, GG and PA to correlate BRAFV600E mutation with BRAFV600E expression and to evaluate their diagnostic and prognostic values. Ninety‐six children were included. BRAFV600E mutation was studied by sequencing and immunohistochemistry; CD34 expression was analyzed by immunohistochemistry. BRAFV600E mutation was detected in PXA (60%), GG (38.7%), DNT (30%, including 3/11 specific and 3/9 non‐specific forms) and PA (12.5%). BRAFV600E expression was recorded in PXA (60%), GG (45.2%) and DNT (30%). CD34 expression was recorded in PXA (60%), GG (58.1%), DNT (25%) and PA (12.5%). Neither CD34 expression nor BRAFV600E status was predictive of prognosis, except for PA tumors where CD34 expression was associated with a shorter overall survival. In conclusion, DNT shared with PXA and GG, BRAFV600E mutation and/or CD34 expression, which represent molecular markers for these tumors, and we recommend searching for CD34 expression and BRAFV600E mutation in all DNT, especially the non‐specific forms.